Value Co‐creation with Stakeholders Using Action Research as a Meta‐methodology in a Funded Research Project. Issue 2 (April 2015) - Dick, Bob; Sankaran, Shankar; Shaw, Kelly; Kelly, Jacqueline; Soar, Jeffrey; Davies, Alan; Banbury, Annie
ABSTRACT A large applied research study is a challenging exercise in project management and is often unpredictable because of its complexity. In the beginning, funding bodies, ethics committees, and participating organizations expect a plan of what is intended. As the research evolves, researchers must meet the expectations of stakeholders while being responsive to the emergent reality that the research faces and partly uncovers. This article describes action research used as an umbrella process that enabled us to manage the research project. We used action research as a meta‐methodology—that is, a process that can subsume multiple subprocesses and under which these contradicting demands can be satisfied. In particular, two characteristics enable action research to do this. One is its cyclic process, iteratively tracing out a rhythm of planning, acting, and observing the results. The other is the nesting of its cycles, applied at scales ranging from the overall study to the moment‐by‐moment facilitation. We illustrate this use of action research with examples from a long‐term applied study of leadership in faith‐based, not‐for‐profit organizations.